Mental health and help seeking among trauma-exposed emergency service staff: a qualitative evidence synthesis. Issue 2 (2nd February 2022) - Auth, Niklas Maximilian; Booker, Matthew James; Wild, Jennifer; Riley, Ruth
Abstract : Objectives: To identify factors and contexts that may contribute to mental health and recovery from psychological difficulties for emergency service workers (ESWs) exposed to occupational trauma, and barriers and facilitators to help-seeking behaviour among trauma-exposed ESWs. Background: ESWs are at greater risk of stressor-related psychopathology than the general population. Exposure to occupational stressors and trauma contribute to the observed rates of post-trauma psychopathology in this occupational group with implications for workforce sustainability. Types of organisational interventions offered to trauma-exposed ESWs are inconsistent across the UK, with uncertainty around how to engage staff. Design: Four databases (OVID MEDLINE, EMBASE, PsycINFO and SCOPUS) were systematically searched from 1 January 1980 to March 2020, with citation tracking and reference chaining. A modified Critical Appraisal Skills Programme tool and quality appraisal prompts were used to identify fatally flawed studies. Qualitative studies of trauma-exposure in front-line ESWs were included, and data were extracted using a customised extraction table. Included studies were analysed using thematic synthesis. Results: A qualitative evidence synthesis was conducted with 24 qualitative studies meeting inclusion criteria, as defined by the PerSPEcTiF framework. Fourteen descriptive themes emerged from this review, categorised into two overarching constructs: (1) factors contributing to mental health (such as the need for downtime, peer support and reassurance) and (2) factors influencing help-seeking behaviour (such as stigma, the content/form/mandatory nature of interventions, and mental health literacy issues including emotional awareness and education). Conclusion: ESWs reported disconnect between the organisations' cultural positioning on trauma-related mental health, the reality of undertaking the role and the perceived applicability and usefulness of trauma interventions. Following traumatic exposure, ESWs identify benefitting from recovery time and informal support from trusted colleagues. A culture which encourages help seeking and open dialogue around mental health may reduce stigma and improve recovery from mental ill health associated with trauma exposure.